Molecular identification and antibiotic control of bacterial contamination in cultures of ginger (Zingiber officinale). Issue 2 (3rd March 2016) - Jain, Anju; Aravindaram, Kandan; Pal, Deepa
ABSTRACT: Zingiber officinale, Rosc., one of the major tropical spices in the world, belongs to the family Zingiberaceae. Bacterial contamination is a major constraint on the cryopreservation of in vitro shoot tip explants. The main objective of this study was to identify the nature of this bacterial contamination and its response to various antimicrobial agents (e.g. the antibiotics cephotaxime and streptomycin sulphate, or copper sulphate) for more effective control. The bacteria isolated from ginger plantlets were identified by amplification and sequencing of their 16S ribosomal DNA, followed by partial sequence analysis. Luteibacter yeojuensis was found in all contaminated cultures. L. yeojuensis is found mainly in soil and as a human pathogen. We believe this is the first report of L. yeojuensis contaminating in vitro cultures of ginger. Among the antimicrobial agents tested in the shoot multiplication medium [i.e. 1.0× Murashige and Skoog salts + 2.5 mg l – l 6-benzylaminopurine + 3% (w/v) sucrose + 0.45% (w/v) Clarigar TM ], 100 mg l – 1 cephotaxime was most effective at reducing bacterial growth. It also gave the maximum number of shoots per shoot bud explant compared to the same medium supplemented with streptomycin sulphate, or CuSO4, or control medium. No further bacterial contamination was observed when 8-week-old cultures were then subcultured on the same medium without added antibiotic or CuSO4 .